Digital Learning Culture di Sekolah Berbasis Boarding School: Studi Adaptasi Siswa Serta Guru Pada Pembelajaran di Sekolah - Widadi, Ahmad Setyo; Rusydiyah, Evi Fatimatur (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2025)
This study aims to explore the digital learning culture at SMP Al Hikmah Boarding School Batu, focusing on the adaptation of students and teachers in technology-based learning processes. A qualitative approach was employed using observation, semi-structured interviews, and documentation. The research informants included the principal, teachers, and active students at the school. The findings indicate that the full integration of the Learning Management System (LMS) in daily teaching and learning activities has transformed learning patterns into more independent, flexible, and interactive ones. Teachers act as facilitators and digital mediators, guiding students to use technology productively and responsibly. However, challenges such as infrastructure limitations and disparities in digital literacy among users remain. Collaborative solutions including regular training, teacher discussion forums, and student mentoring are key factors for successfully fostering an inclusive and sustainable digital learning culture. This study is expected to serve as a reference for boarding schools in optimizing digital learning implementation.